Recent Developments on the Incentives for Users’ to Participate in Vehicle-to-Grid Services - Davide Astolfi; Antony Vasile; Silvia Iuliano; Marco Pasetti (Energies)
The transportation is the sector of human activities which contributes the most to greenhouse gas emissions by far [...]